2004
DOI: 10.1017/s1047951104005062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of neonatal cardiac hypertrophy and its regression

Abstract: Neonatal cardiac hypertrophy associated with diabetic pregnancy is transient and regresses naturally, but is associated with increased morbidity and mortality. This study was undertaken to analyse the changes in expression of 5 cardiac genes, including atrial natriuretic peptide, alpha- and beta-myosin heavy chain, and cardiac and skeletal alpha-actin genes, using a rat neonatal model, in which cardiac hypertrophy was induced via maternal diabetes. In the hypertrophied left ventricle of neonates from diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The role of NPR-A in inhibiting cardiac hypertrophy seems to be even more important in the presence of hypoxia (23). Gopinath et al (24) found that mRNA levels for the atrial natriuretic peptide gene were significantly higher in left ventricular tissue from neonates of diabetic mothers than from those control mothers, followed by an 18-fold decrease in mRNA from the 1st to the 28th neonatal day in comparison with a fivefold decrease in the control neonates during the same time with no difference between the cohorts by day 28. This model fits with the regression in diabetic cardiomyopathy that is usually seen in the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…The role of NPR-A in inhibiting cardiac hypertrophy seems to be even more important in the presence of hypoxia (23). Gopinath et al (24) found that mRNA levels for the atrial natriuretic peptide gene were significantly higher in left ventricular tissue from neonates of diabetic mothers than from those control mothers, followed by an 18-fold decrease in mRNA from the 1st to the 28th neonatal day in comparison with a fivefold decrease in the control neonates during the same time with no difference between the cohorts by day 28. This model fits with the regression in diabetic cardiomyopathy that is usually seen in the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…In aryl hydrocarbon receptor-null mouse embryos that develop cardiac hypertrophy, atrial natriuretic factor gene expression is upregulated on 14.5 days gestation (22). In addition, studies on rats have shown that neonates from diabetic dams have significant cardiac hypertrophy and about 4-fold higher ventricular expression of ANP mRNA compared with control group neonates (12). They found about 18-fold decrease in ANP mRNA expression in the neonates of diabetic pregnancies from the 1st to the 28th day in comparison with a 5-fold decrease in the controls during the same period (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on rats have shown that neonates from diabetic dams have significant cardiac hypertrophy and about 4-fold higher ventricular expression of ANP mRNA compared with control group neonates (12). They found about 18-fold decrease in ANP mRNA expression in the neonates of diabetic pregnancies from the 1st to the 28th day in comparison with a 5-fold decrease in the controls during the same period (12). These experimental studies support our findings, which show significantly elevated NT-proANP and NT-proBNP concentrations in fetuses born to diabetic mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of molecular biological techniques has provided evidence that the hearts of preterm neonates treated with corticosteroids feature an increase in alpha chains of myosin and a reduction in beta one, an event similar to that observed in the case of cardiac hypertrophy in neonates born from a diabetic mother. 70…”
Section: Cvr In Preterm Neonates Subjected To Corticosteroid Therapymentioning
confidence: 99%